Words and structures refer in Alms Studying Languagal - المدرس المساعد أنسام خضیر خلیل (College of Education for Women, 2019)
Alms (or Zakat) is one of the Pillar of Islam and it was atask imposed on Muslims. Becomes of the importance of this task and its influence on the human Psychic in particular and on the Society in general this study aims at Studying the words that it refers to in the Holy Quran, At the beginning the researcher has introduced the words it refers to, and the significance of each in the Holy Quran and the Speciality of each one of such words, then the Structures they donet have been also introduced, whether such structures are descriptive, adverbial or verbal.This was introduced in addition to explaining the influence of changing the Shape of such words in emphasizing the meaning and the influence of Portraiting style in bending the human psyche, such the Holy Quran tends to be used in different places to achieve religious and secular purposes.